Financial services firms governance, regulations, valuations, mergers, and acquisitions - Rezaee, Zabihollah, 1953-; Rezaee, Zabihollah, 1953-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Indispensable coverage of new federal regulatory reforms and federal financial issuesAn essential guide covering new federal regulatory reforms and federal financial issuesFinancial Institutions, Valuations, Mergers and Acquisitions, Third Edition presents a new regulatory framework for financial institutions in the post-bailout era. Provides valuable guidance to assess risks, measure performance and conduct valuations processes to create shareholder value Covers the protection of other stakeholders, including customers, regulators, government, and consumers Offers an up-to-date understanding of financial institutions, their challenges, and their opportunities in the post-Sarbanes-Oxley era Over the past decade, substantial changes have taken place in the structure and range of products and services provided by the financial services industry. Get current coverage of these changes that have transformed both traditional organizations such as banks, thrifts, and insurance companies, as well as securities providers, asset management companies and financial holding companies with the up-to-the-minute coverage found in Financial Institutions, Valuations, Mergers and Acquisitions, Third Edition"--
pt. 1. Financial services industry : its markets, regulations, and governance -- pt. 2. The foundation : financial institutions, valuations, mergers, acquisitions, and regulatory and accounting environment -- pt. 3. Fundamentals of valuations : concepts, standards, and techniques -- pt. 4. Assessment of financial institutions -- pt. 5. Valuation of mergers and acquisitions.
Rev. ed. of : Financial institutions, valuations, mergers, and acquisitions. 2nd ed. New York : J. Wiley, c2001.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Banks and banking -- Valuation -- United States; Bank mergers -- United States; Sale of banks -- United States; Financial institutions -- Valuation -- United States; Financial institutions -- Mergers -- United States; Financial institutions -- Purchasing -- United States; Consolidation and merger of corporations -- Law and legislation -- United States; Electronic books